System dynamic approach for management of urban parks: a case study - Lucia Tamburino; Valentina La Morgia; Ezio Venturino (Computational Ecology and Software, 2012)
Public agencies tackling the issues of natural resource management need objective analysis to anticipate the ecosystem consequences of their actions. Mathematical models can be regarded as an effective tool to support decision makers in this context because of their predictive capacity and of their ability to describe complex natural systems. In particular, the aim of this paper is to show how mathematical modelling and simulation can be applied in the field of urban park management. As an example, we consider a case study where a domestic herbivore, the sheep, was introduced as a natural regulator of grass growth. The results show that the introduction of sheep is not currently sustainable and that it should be complemented by other measures in order to tackle both the issue of regulating grass growth and to prevent debarking of the newly planted trees.